2015
DOI: 10.1038/cmi.2015.64
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming HBV immune tolerance to eliminate HBsAg-positive hepatocytes via pre-administration of GM-CSF as a novel adjuvant for a hepatitis B vaccine in HBV transgenic mice

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) is known to be a potential vaccine adjuvant despite contradictory results from animal and human studies. The discrepancies may be due to the different doses and regimens of GM-CSF that were used, given that either mature or immature dendritic cells (DCs) could be induced under different conditions. To test the hypothesis that GM-CSF can be used as a novel adjuvant for a hepatitis B virus (HBV) therapeutic vaccine, we administered GM-CSF once per day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 62 publications
(65 reference statements)
2
31
0
Order By: Relevance
“…In vivo cytotoxic lysis assay was conducted as described previously. 18 Briefly, splenocytes from naïve C57BL/6 donor mice were labeled with 15 μM of CFSE and pulsed with 1 μg/mL of S 208–215 (defined as CFSE high target cells). An equal fraction of splenocytes were labeled with 1 μM of CFSE and pulsed with 1 μg/mL of OVA 257–264 (defined as CFSE low target cells) as a non-HBV target control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo cytotoxic lysis assay was conducted as described previously. 18 Briefly, splenocytes from naïve C57BL/6 donor mice were labeled with 15 μM of CFSE and pulsed with 1 μg/mL of S 208–215 (defined as CFSE high target cells). An equal fraction of splenocytes were labeled with 1 μM of CFSE and pulsed with 1 μg/mL of OVA 257–264 (defined as CFSE low target cells) as a non-HBV target control.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, we observed that the 3 × GM-CSF+VACCINE treatment achieved 90% reduction of HBsAg level in the model via the activation of HBsAg specific CD8 + T cells. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Although HBV-transgenic mice, which was reported to persistently express distinct HBV antigens or produce infectious virions (Chisari et al, 1987 ; Wirth et al, 1995 ; Schirmbeck et al, 2000 ), have been used to study HBV immunopathogenesis and test numerous drugs for HBV infection, they are inherently tolerant to transgene products (Araki et al, 1989 ; Moriyama et al, 1990 ; Guidotti et al, 1995 ; Larkin et al, 1999 ; Wang et al, 2016 ). Therefore, the model is not suitable for studying HBV vaccines.…”
Section: Establishment Of Viral Hepatitis Models By Hgdmentioning
confidence: 99%
“…The undesirable negative impact of GM-CSF as an adjuvant was solved by using our recently published protocol in which 3-day pretreatments with GM-CSF were given before a vaccination into the same site of animals to elicit potent immune responses. This protocol overcame the immune tolerance and over 90% reduction of HBsAg level was observed in the HBsAg transgenic mouse model [ 28 ]. While the outcome remains exciting, the protocol by its original design was too complex for potential use in humans as a therapeutic vaccine.…”
Section: Introductionmentioning
confidence: 99%